2012
DOI: 10.1371/journal.pone.0029482
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition and Functional Neuroimaging Help to Discriminate Healthy Adolescents at Risk for Mood Disorders from Low Risk Adolescents

Abstract: IntroductionThere are no known biological measures that accurately predict future development of psychiatric disorders in individual at-risk adolescents. We investigated whether machine learning and fMRI could help to: 1. differentiate healthy adolescents genetically at-risk for bipolar disorder and other Axis I psychiatric disorders from healthy adolescents at low risk of developing these disorders; 2. identify those healthy genetically at-risk adolescents who were most likely to develop future Axis I disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 34 publications
2
49
0
Order By: Relevance
“…Only 5 recent studies have tried to overcome this issue by introducing individual confidence measures. 39,48,54,56,57 As seen in Fig 2 and On-line larger body of independent work. The diversity of scientific backgrounds of recent studies is reflected by a striking heterogeneity of reported methodologic details, sample characteristics, validation strategies, and performance measures.…”
Section: Potential Clinical Applications and Integration In Diagnostisupporting
confidence: 55%
“…Only 5 recent studies have tried to overcome this issue by introducing individual confidence measures. 39,48,54,56,57 As seen in Fig 2 and On-line larger body of independent work. The diversity of scientific backgrounds of recent studies is reflected by a striking heterogeneity of reported methodologic details, sample characteristics, validation strategies, and performance measures.…”
Section: Potential Clinical Applications and Integration In Diagnostisupporting
confidence: 55%
“…Previous feature selection applications using RFE in neuroimaging classification tasks include; ASD (Calderoni et al 2012; Duchesnay et al 2011; Ecker et al 2010; Ingalhalikar et al 2011), MDD (Craddock et al, 2009), schizophrenia (Castro et al 2011b), psychosis (Gothelf et al 2011), object recognition in a fMRI task (Hanson and Halchenko, 2008), fragile X syndrome (Hoeft et al 2011), ADHD (Marquand et al 2011), MCI (Nho et al 2010), fMRI spatial patterns (De Martino et al 2008), mood disorders (Mourao-Miranda et al 2012) and AD (Davatzikos et al 2008; Mesrob et al 2008). An interesting variant of RFE, which involves backward-elimination of voxel clusters rather than individual features, has recently been explored (Deshpande et al 2010).…”
Section: 0 Supervised Feature Reduction Techniquesmentioning
confidence: 99%
“…Additional exclusion criteria for all participants were: Wechsler Intelligence Test score <80 (Wechsler, 1999), neurological disorders, history of head trauma, medical conditions including epilepsy, stroke, diabetes, lupus and other vascular disorders, substance abuse/dependence, pregnancy, or presence of metal in the body that would contradict an MRI. Imaging data for the depressed adolescents and a subset of the healthy offspring (Mood-risk and HC) recruited into this study have been published previously using this task, with happy and angry faces (Pan et al, 2013) and with happy and fearful faces (Mourao-Miranda et al, 2012), respectively. All participants were scanned at the Brain Imaging Research Center, Pittsburgh and underwent the same imaging protocol (see below).…”
Section: Methodsmentioning
confidence: 99%